THE AL-MUNAWWARAH MODEL; CASE STUDY ON INSTITUTIONALIZING PROPHETIC LEADERSHIP TO FOSTER AN EXCELLENT ORGANIZATIONAL CULTURE - Istibsyaroh; Saiful Hadi; Aziz, Abdul; Atiqullah; Hurriyatul Ifadhah, (re-JIEM (Research Journal of Islamic Education Management), 2025)
Many Islamic educational institutions face the challenge of translating the noble values of prophetic leadership into effective operational strategies. This research addresses this gap by analyzing the strengthening model of prophetic leadership in building an excellent organizational culture at Al-Munawwarah Islamic Elementary School. Through a descriptive qualitative approach, this study finds that leadership effectiveness is not merely conceptual but is manifested in specific policies. Among these are the systematic integration of Islamic values into the national curriculum, the implementation of consistent disciplinary rules for teachers and students, such as the use of a public tardiness list, and the development of a collaborative culture through intensive vision communication and motivation. As a result, an educational environment that measurably supports the formation of students' moral character is established. This study offers a practical contribution in the form of an implementable framework, demonstrating how prophetic leadership principles can be translated into tangible programs and policies, making it replicable for other educational institutions.